2024
DOI: 10.1002/ange.202402436
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Upcycling and Depolymerization of Vinyl Polymers

Kostas Parkatzidis,
Hyun Suk Wang,
Athina Anastasaki

Abstract: Photocatalytic upcycling and depolymerization of vinyl polymers have emerged as promising strategies to combat plastic pollution and promote a circular economy. This mini review critically summarizes current developments in the upcycling and degradation of vinyl polymers including polystyrene and poly(meth)acrylates. Of these material classes, polymethacrylates also possess the unique possibility to undergo a photocatalytic depolymerization back to monomer under thermodynamically favourable conditions, thus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Here, we focus on step-growth polymers (SGPs), while recognizing the equal significance of chain-growth polymers. With regards to the delineation and recycling of the latter, it can be referred in these comprehensive reviews. …”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on step-growth polymers (SGPs), while recognizing the equal significance of chain-growth polymers. With regards to the delineation and recycling of the latter, it can be referred in these comprehensive reviews. …”
Section: Introductionmentioning
confidence: 99%
“…With the advent of reversible deactivation radical polymerization (RDRP), the synthesis of polymers with controlled dispersity, architecture, sequence, and end-group fidelity has become commonplace. The possibility to pre-install labile end-groups, usually halogens or thiocarbonylthio compounds, not only enables the formation of well-defined block copolymers but also creates the opportunity to trigger low-temperature depolymerization for ATRP- or reversible addition–fragmentation chain transfer (RAFT)-synthesized materials. While earlier reports revealed low monomer conversions during the depolymerization of bulky monomers, subsequent reports sought to intentionally encourage depolymerization under thermodynamically favorable conditions. Ouchi and co-workers first showed that poly­(methyl methacrylate) (PMMA) synthesized by ATRP could be depolymerized back to monomers in the presence of ruthenium catalysts, although prevalent side reactions limited the overall monomer regeneration . The group of Matyjaszewski highlighted the importance of a chlorine end-group to suppress lactonization at high temperatures when either copper or iron catalysts were employed. , Our group subsequently showed that bromine-terminated polymers can also be efficiently depolymerized if end-group activation dominates over lactonization .…”
mentioning
confidence: 99%